A CONTENT ANALYSIS OF ENGLISH TEXTBOOK ENTITLED “WHEN ENGLISH RINGS A BELL” - Widyastuti, Iin; Syam, Andi Tenrisanna; Yahya, Amalia (English Language Teaching Methodology, 2024)
The purpose of this research is to evaluate the suitability of the materials in the English textbook titled "When English Rings A Bell" for second-grade junior high school students at UPT SMP Negeri 1 Tana Lili, in terms of content, language, and presentation as determined by BSNP (Badan Standar Nasional Pendidikan). This study employs content analysis methodology, with researchers acting as human instruments. The instrument was completed using several statement items in a checklist based on BSNP's textbook evaluation criteria. The results indicate that the textbook is systematic, balanced, and student-centred, supporting autonomous learning and self-evaluation. However, continuous improvements are necessary to optimize its content and presentation fully.